Characterization, modeling and simulation of fused deposition modeling fabricated part surfaces. (27th October 2017) - Taufik, Mohammad; Jain, Prashant K
Abstract: Surface roughness is generally used for characterization, modeling and simulation of fused deposition modeling (FDM) fabricated part surfaces. But the average surface roughness is not able to provide the insight of surface characteristics with sharp peaks and deep valleys. It deals in the average sense for all types of surfaces, including FDM fabricated surfaces with distinct surface profile features. The present research work shows that kurtosis and skewness can be used for characterization, modeling and simulation of FDM surfaces because these roughness parameters have the ability to characterize a surface with sharp peaks and deep valleys. It can be critical in certain application areas in tribology and biomedicine, where the surface profile plays an important role. Thus, in this study along with surface roughness, skewness and kurtosis are considered to show a novel strategy to provide new transferable knowledge about FDM fabricated part surfaces. The results suggest that the surface roughness, skewness and kurtosis are significantly different at 0° and in the range (0°, 30°], [30°, 90°] of build orientation.